Regime Change: The Need for Scientific Critical Consciousness - Usama Javed Mirza (International Journal of Critical Diversity Studies)
Concerns about nuclear technology or global warming are among myriad socio-scientific issues in the world that students are given very poor preparation with which to engage critically. By not tackling them head-on, curricula risk dangerously misleading students about the nature of science, its legacy and place in the world; aggravating socio-economic inequality perpetuated by centuries of European colonialism of the Global South. These misleading ideas include Eurocentrism, viewing religion as irrational and Western science as superior to indigenous knowledge systems. In an effort to identify how to inculcate the dispositions in students to counter oppressive ideas taught under the guise of science, this paper presents a theoretical framework and curriculum for inculcating a scientific critical consciousness (SCC). SCC is presented as the ability to perceive these oppressive ideas relating to science, and to take action to counter them. The theoretical framework is developed by adapting ideas from and critiques of Freire (2017) , Greene (2011) , Boler and Zembylas (2002) , Anyon (2009) and Biesta (1998) . This article outlines how the curriculum, teaching and assessment methodologies of traditional science classes can be enhanced to inculcate SCC. This is illustrated by presenting a “revamped” curriculum of the Cambridge Assessment International Education (CAIE) O’ level physics, complete with a learning outcomes and assessment framework. Parts of this curriculum were informally pre-piloted at a private school in Islamabad, Pakistan, and at a public school in Harlem, New York. These pre-pilot experiences confirm the challenges predicted by research in implementing emancipatory curricula, e.g. that social taboos prevent open discussion of sensitive socio-scientific social justice issues. They also indicate much promise from even partial inclusion; students demonstrated changing perspectives and motivation to tackle social justice issues, and there was significantly increased student engagement—including by those who were previously disinterested in science.